2016
DOI: 10.1051/0004-6361/201528043
|View full text |Cite
|
Sign up to set email alerts
|

Temperature condensation trend in the debris-disk binary systemζ2Reticuli

Abstract: Context. Detailed abundance studies have reported different trends between samples of stars with and without planets, possibly related to the planet formation process. Whether these differences are still present between samples of stars with and without debris disk is still unclear. Aims. We explore condensation temperature T c trends in the unique binary system ζ 1 Ret − ζ 2 Ret to determine whether there is a depletion of refractories that could be related to the planet formation process. The star ζ 2 Ret ho… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
55
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(59 citation statements)
references
References 69 publications
3
55
0
Order By: Relevance
“…This very exciting and important (possible) connection between chemical peculiarities and formation of planets has also been examined in other works (e.g. Takeda et al 2001;Ecuvillon et al 2006;Sozzetti et al 2006;Schuler et al 2011b;González Hernández et al 2013;Maldonado et al 2015;Nissen 2015;Biazzo et al 2015;Saffe et al 2015Saffe et al , 2016, but contradictory conclusions were reached.…”
Section: Introductionmentioning
confidence: 69%
See 2 more Smart Citations
“…This very exciting and important (possible) connection between chemical peculiarities and formation of planets has also been examined in other works (e.g. Takeda et al 2001;Ecuvillon et al 2006;Sozzetti et al 2006;Schuler et al 2011b;González Hernández et al 2013;Maldonado et al 2015;Nissen 2015;Biazzo et al 2015;Saffe et al 2015Saffe et al , 2016, but contradictory conclusions were reached.…”
Section: Introductionmentioning
confidence: 69%
“…The main reason for using [X/Fe] instead of [X/H] is to be able to remove the trends related to the Galactic chemical evolution (GCE) from the [X/Fe]−[Fe/H] relations (e.g. González Hernández et al 2013;Saffe et al 2016;Liu et al 2016). Recently, some authors used the [X/Fe]−age relation to correct for the GCE (e.g.…”
Section: T C Slopementioning
confidence: 99%
See 1 more Smart Citation
“…The 50% T c equilibrium condensation temperatures for a gas of solar system composition are taken from Lodders (2003). It is common practice to plot [X/Fe] (and not just [X/H]) versus T c , which allows us to remove the trends related to Galactic chemical evolution (e.g., González Hernández et al 2013;Saffe et al 2016). Although this procedure can be justified when stars with different metallicities are compared, it can produce a bias in the derived slope.…”
Section: T C Slopementioning
confidence: 99%
“…Several studies have shown that there may be small differences in the chemical composition of their components, possibly due to the planet formation process (Gratton et al 2001;Desidera et al 2004Desidera et al , 2006. The similarity between the two components of a binary system enabled achieving a higher precision in a differential study (e.g., Saffe et al 2015Saffe et al , 2016. To date, more than 2700 planetary systems have been reported 2 , but only a handful of these systems are binaries with similar components.…”
Section: Introductionmentioning
confidence: 99%